Redactie de Blauwe Vaan. V.l.n.r.: Ploeg, Stekelenburg en v.d.Meulen. Foto eind 1941 of 1942 - Kramer, J.H.H.,
Redactie de Blauwe Vaan. V.l.n.r.: Ploeg, Stekelenburg en v.d.Meulen. Foto eind 1941 of 1942.